Small and Medium Enterprises, Central Business District (CBD) for Accelerating of Regional Development - Sudapet, Nyoman; Sukoco, Agus; Ikhsan Setiawan, Muhammad; Halim, Paisal; Badruddin, Syamsiah; ., Tuswoyo; Hidayat, Ahmad; Napitupulu, Darmawan; Abdullah, Dahlan; Saleh A, A (International Journal of Engineering and Technology, 2018)
Madura is small island, East Java Province, Indonesia, with the Surabaya - Madura (Suramadu) Bridge 5.7 km length. It is the largest bridges In Indonesia, connected 2 (two) island, Java and Madura. In Suramadu area will be build landed house and apartments, residential, central of business, central of tourism. In Suramadu area, especially in Surabaya side will be built by some interesting landed house and apartments, residential, central of business, central of tourism, combining with recreation area. The Government seeks to attract the private sector to cooperate in the development and investment in landed house and apartments, residential, central of business, central of tourism, through the approach of government and private cooperation. Law number 22/1999 and Law number 34/2004 on regional autonomy have improved the performance of local governments, in particular through the policy of increasing local revenues through cooperation with private parties. Investment must be injected in Suramadu area by investors is IDR 18,410,577,670,000.00, it would be very interesting.Â Â Â